A Survey of Source Routing Protocols, Vulnerabilities and Security In Wireless Ad-hoc Networks - Kolla, Srihari Babu; Prasad, B.B.K (International Journal of Computer Sciences and Engineering, 2014)
A wireless Adhoc networks is the collection of wireless nodes that can co-operate by forwarding packets for each other to allow nodes to communicate directly. The deployment of Ad-hoc networks in security- and- safety in critical environments requires secure communication primitives. As WSNï¿½s become more and more crucial to everyday functioning of the people. Securing in wireless ad-hoc networks is a challenging task. Low power wireless networks are an existing research direction in routing and security. This paper discusses a wide variety of vulnerabilities while routing and different existing securities to mitigate them.